PENGARUH RASIO LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PERUSAHAAN FOOD AND BEVERAGE - Febrianto, Eris Dwi Agung; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to analyze the financial ratio particularly the liquidity ratio and solvability ratio with sales growth and firm size as the control variable which have influence to the profitability of the company which has been measured by using the return on asset (ROA). The population is the food and beverages companies which are listed in IDX in 2010-2013 periods. The sample has been collected by performing purposive sampling method and 9 companies have been selected as samples. The influence of independent variables i.e.: account receivable turnover, inventory turnover, current ratio, debt to equity ratio, sales growth and firm size to the ROA which is studied by using multiple linear regressions method. The result of the research shows that only inventory turnover variable which has significant influence to the ROA. Meanwhile, the other 5 variables i.e.: account receivable turnover, current ratio, debt to equity ratio, sales growth and firm size do not have any influence to the ROA. It means that only inventory turnover can influence the profitability of the company during the years of 2010-2013 on food and beverages companies which are listed in Indonesia Stock Exchange whereas other variables do not have any influence in achieving profit.Keywords: Liquidity Ratio, Solvability Ratio, Profitability Ratio